PENGEMBANGAN MEDIA POWERPOINT INTERAKTIF BERBASIS KEARIFAN LOKAL GORONTALO DALAM MENINGKATKAN KEMAMPUAN MEMAHAMI KONSEP OPERASI HITUNG BILANGAN BULAT - Hasdin Ahmad; Fatimah Djafar; Miftha Huljannah (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
This study aims to determine the stages of development analysis, design, development process, and the level of validity, practicality, and effectiveness of interactive PowerPoint media based on Gorontalo local wisdom in learning integer arithmetic operations material for sixth grade students of SDN 04 Limboto. This type of research is development research using the ADDIE Analyze, Design, Develop, Implement, and Evaluate model. The subjects of the field trial were sixth grade students of SDN 04 Limboto. In this study, the instruments used in collecting data were questionnaires, tests, interview guidelines, and expert validation instruments. Based on the results of the research, the interactive PowerPoint media based on Gorontalo local wisdom that was developed obtained a level of validity with a very valid category based on the results of the assessment of media experts and material experts. The level of practicality of the media based on the questionnaire responses of teachers and students was in the very practical category. This is indicated by the increase in student learning outcomes between pretest and posttest scores, the results of the paired sample t-test with a significance value (Sig. 2-tailed) of 0.00 < 0.05, and the average N-Gain value of 0.62 which is in the moderate category and is included in the fairly effective category. Thus, interactive PowerPoint media based on Gorontalo local wisdom is suitable for use in mathematics learning in grade VI of elementary school.